The creative style of C.W. Harrison and J.L. Humphreys in Malay pantun translation - Shunmugam, Krishnavanie (Journal of Modern Languages, 2015)
Malay pantuns were brought to the centre stage of literary awareness in early 20th century British Malaya via creative English translations produced by three British officials that is J.W. Wilkinson, Sir R.O. Winstedt and A.W. Hamilton. To this day, their lively English renditions of the Malay pantun are often quoted by Malaysian pantun scholars and enthusiasts. In contrast to these British stalwarts of the Malay pantun, there were two other British administrators, namely C.W. Harrison and J.L. Humphreys, whose English translations of the pantun are little or hardly known but which showcase a vibrancy no less than the translations by Wilkinson, Winstedt and Hamilton. This paper aims to highlight the distinct creative traits of these two obscure British translators of the pantun. The translation of the pithy, rhythmic pantun is no easy task, especially if one wishes to recreate its aesthetics and condensed wisdom. The paper shows how Harrison and Humphreys, like their contemporaries, are able to achieve this through their creatively modulated translations of the Malay pantun.